Some assembly required: tracing the interpretative work of Clinical Competency Committees. - Pack, Rachael; Lingard, Lorelei; Watling, Christopher J; Chahine, Saad; Cristancho, Sayra M (Medical Education, 2019)
Objectives: This qualitative study describes the social processes of evidence interpretation employed by Clinical Competency Committees (CCCs), explicating how they interpret, grapple with and weigh assessment data. Methods: Over 8 months, two researchers observed 10 CCC meetings across four postgraduate programmes at a Canadian medical school, spanning over 25 hours and 100 individual decisions. After each CCC meeting, a semi‐structured interview was conducted with one member. Following constructivist grounded theory methodology, data collection and inductive analysis were conducted iteratively. Results: Members of the CCCs held an assumption that they would be presented with high‐quality assessment data that would enable them to make systematic and transparent decisions. This assumption was frequently challenged by the discovery of what we have termed 'problematic evidence' (evidence that CCC members struggled to meaningful interpret) within the catalogue of learner data. When CCCs were confronted with 'problematic evidence', they engaged in lengthy, effortful discussions aided by contextual data in order to make meaning of the evidence in question. This process of effortful discussion enabled CCCs to arrive at progression decisions that were informed by, rather than ignored, problematic evidence. Conclusions: Small groups involved in the review of trainee assessment data should be prepared to encounter evidence that is uncertain, absent, incomplete, or otherwise difficult to interpret, and should openly discuss strategies for addressing these challenges. The answer to the problem of effortful processes of data interpretation and problematic evidence is not as simple as generating more data with strong psychometric properties. Rather, it involves grappling with the discrepancies between our interpretive frameworks and the inescapably subjective nature of assessment data and judgement. The authors of this qualitative study illustrate the processes of evidence interpretation Clinical Competency Committees (CCCs) use to grapple with and weigh assessment data.